INTEGRASI PEMBENTUKAN KARAKTER DALAM PEMBELAJARAN IPS SD - Harsanti, Arni Gemilang (Premiere Educandum, 2015)
The ministry of national education (kemendiknas) stated the application of character education in every level from Elementary School to University. It is because during these days, educational world scored less succeed in introducing national generation to become prestige personality. It is implicated through every subject of study, like social studies. The position of social studies learning is so unique because there must be preparation to educate students to live and understand their world, where their personal and social quality will become more important. The developed values in character education are identified by: (1) religion, (2) Pancasila, (3) Cultural, and (4) National education purposes. The value of social studies, a teacher must push the students to become active in obtaining values. Through social studies, students are directed to be democratic and responsible citizen and also world citizen who love peaceful. The subject of social studies is designed to develop science, understanding and analysis ability to social community condition in entering dynamic society life.Â Keywords : Character Formation, Learning, Social Studies, Basic Education